MOVEMENT DISORDER CAUSED BY HYPEROSMOLR HYPERGLYCEMIC STATE IN AN OLDER ADULT: A CASE REPORT - Raíssa Katherine Rodrigues; Leandro Augusto Rocha; Marcelo Perim Baldo; Michelle Aparecida Ribeiro Borges; Ronaldo Urias Mendonça; Simone de Melo Costa; Luciana Colares Maia (Brazilian Society of Geriatrics and Gerontology, 2020)
Diabetes mellitus (DM) and its complications constitute the leading causes of early mortality in most countries. Population aging and the growing prevalence of obesity and sedentary lifestyles, in addition to spreading urbanization, are considered the main drivers of the increasing incidence and prevalence of DM worldwide. This case report describes the acute onset of movement disorder in an older woman secondary to hyperosmolar hyperglycemic state (HHS). The combination of hemichorea-hemiballismus, HHS, and evidence of basal ganglia involvement on neuroimaging is considered a unique syndrome. Movement disorders secondary to HHS respond satisfactorily to administration of neuroleptic agents and proper glycemic control. The lack of published studies on this pathologic entity may lead to clinical and laboratory underdiagnosis, with negative impacts on patient prognosis and follow-up.